Online Student Admission Application at SMK Al-Basyariah Bojong Gede - Muthia, Dinda Ayu; Ramadhani, Andini; Kurniawan, Adi; Irfansyah, Raka (Politeknik Ganesha Medan, 2019)
Acceptance of new students is one of the processes that exist in educational institutions every year, the number of prospective students who register causes the new student admission committee cannot manage everything properly so that it is less effective in handling it. In this study, the new student admission system used by Al-Basyariah Vocational School Bojong Gede still uses the system manually, which still uses paper records, so that minimal damage and even data loss occurs. Making a new student registration information system is expected to facilitate new prospective students in registering by saving time and costs compared to coming directly to school and with the information system of new student admissions, it is expected to help and simplify the processing of students in this school.